PENGARUH PIJAT OKSITOSIN TERHADAP PENINGKATAN PRODUKSI ASI IBU MENYUSUI DI PUSKESMAS PLUS MANDIANGIN - Delima, Mera; Arni, Gina Zulfia; Rosya, Ernalinda (Jurnal Ipteks Terapan, 2015)
This study is based on interviews conducted with 3 breastfeeding mothers and the amount of milk her breast is little caused crying baby and mothers milk punting blisters. Meanwhile, two other women told her normal milk production. The mother said the lack of information that were made of treatments to improve the production of breast milk (ASI) and they do not know aboutÂ  massage oxytocin to help increase milk production. This study aimed to observe the effect of oxytocin massage to increase milk production of breastfeeding mother in Plus Mandiangin Public Health Center Bukittinggi 2016. The study design using quasi experimental method, with the approach of one group pretest and posttest. Retrieving data using a questionnaire containing questions regarding milk production mother lactating. The research sample is 21 people who were in Plus Mandiangin Public Health Center Bukittinggi. In this study showed that there is a massage effect of oxytocin to increase milk production of breastfeeding mother inÂ  Plus Mandiangin Public Health Center Bukittinggi 2016 with a p-value of 0.000. It was concluded that there is a massage effect of oxytocin to increase milk production of breastfeeding mother in Plus Mandiangin Public Health Center Bukittinggi 2016. It is expected that this study can be used as a therapy to increase milk production of breastfeeding mothers.